REPRESENTASI MUATAN LITERASI EMOSI DALAM BUKU BAHASA INDONESIA KURIKULUM MERDEKA KELAS V SEKOLAH DASAR - Alya Fanani; Seni Apriliya; Ahmad Mulyadiprana (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the representation of emotional literacy content in the Indonesian language textbook Bahasa Indonesia: Bergerak Bersama for fifth-grade elementary school students in the Merdeka Curriculum. The study employed a qualitative approach using content analysis of reading texts, dialogues, illustrations, and learning activities in the textbook based on Steiner’s (2003) emotional literacy theory. Data were collected through documentation study and analyzed using thematic analysis by Braun and Clarke (2006). The results showed that the textbook contains five aspects of emotional literacy, namely self-awareness of emotions, empathy, emotional management, repairing emotional damage, and building social interaction. Self-awareness of emotions was the most dominant aspect, while repairing emotional damage was the least represented aspect. The findings indicate that the textbook has integrated emotional literacy values through characters, social interactions, and learning situations related to students’ daily lives. However, the limited representation of emotional management and social conflict resolution provides students with only a few examples of socio-emotional behavior in learning texts. Therefore, it is necessary to develop learning texts that accommodate emotional literacy aspects more proportionally in order to support students’ socio-emotional development more optimally.